Effect of Addition Zirconia/Chitosan Filler on Mechanical Properties of Heat Cure Polymethyl Methacrylate Resin - Shahad Lateef Mohammed1 / Firas Abdulameer Farhan2 ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The preferred material for creating removable prosthesis is acrylic resin. for the reintegration of edentulous patients due to its good aesthetics, precise fit, low cost of equipment, and ease of clinical and laboratory manipulation. Acrylic resin exhibited relatively unsatisfactory characteristics like low impact and transverse strength. However, the acrylic resin was reinforced by adding filler materials like glass fibers or mixing two powders like zirconia and chitosan. The goal of this investigation was to explore how adding nanoscale zirconia with micrometer size of chitosan (zr-ch) filler with two percentages of 1% wt. and 5% wt. and two ratios of zr-ch (2:1 and 1:2) according to a pilot study and evaluate the surface hardness,  impact and transverse strength .Ninety heat-cure acrylic samples were divided into three groups (each group 30 samples) based on the percentage weight of filler added to the acrylic mixture and the ratio between the nanoparticles of zirconia with a micrometer of chitosan particles. For control group (c) without addition, group A1 with 1% wt. and a ratio of 2:1 (zr-ch) and group A2 with 5% wt. and a ratio of 1:2. Each group was tested with impact strength, transverse strength and surface hardness (10 samples for each test). The zr-ch mixture ratio was prepared and selected according to the pilot study. A sharpy testing device was used to measure the impact strength while a hardness shore D device measured surface hardness and the final test was transverse strength which was tested by a universal Instron machine. The data were statistically analyzed by IBM SPSS statistics (version 24). The findings of the present study showed significant differences in surface hardness and transverse strength throughout the various study groups. However, the group A2 variation in impact strength was discovered to be nonsignificant, while the group A1 difference was shown to be significant. The best result for all three tests was obtained in the group A1. The adding zr-ch mixture improved surface hardness, impact and transverse strength, which improved acrylic denture base.